Examining the impact of generation Z's attitude toward counterfeit footwear in Malaysia - Lim, Su Kim (2024)
The research study is developed to examining the impact of Generation Z’s attitude toward counterfeit footwear in Malaysia. The main concern of this research will be around the identified price-quality inference, perceived risks, personal gratification, and value consciousness that impact Generation Z’s attitude toward counterfeit footwear. There are four hypotheses constructed to study and generate comprehensive results.